XORIJIY TIL O’QITUVCHISI IJTIMOIY PSIXOLOGIK BILIMDONLIGINI OSHIRISHDA PEDAGOGIK MULOQOTNING AHAMIYATI - Sayfullaev Xurshid, Sayfullaev Xurshid (Журнал иностранных языков и лингвистики, 2021)
This article describes the importance of creative communication in improving the social psychological knowledge of a foreign language teacher. Professional-pedagogical communication is a complex phenomenon. The article emphasizes pedagogical communication as an integral quality of pedagogical influence. It is a professional dialogue between teacher and student in the educational process, in which information is exchanged and the educational impact is exerted on the student.